Pyogenic granuloma of the epiglottis: a case report - Karlidag, T.; Yalcin, S.; Akpolat, N.; Yildiz, M. (Galenos Yayincilik, 2007)
The pyogenic granuloma is a benign vascular lesion of the skin and mucous membranes that frequently seen in the head and neck. The etiology of this lesion remains unknown but trauma, gingival and periodontal diseases, bad oral hygiene, viral or fungal infections are considered in the etiology of pyogenic granuloma. The majority of pyogenic granulomas are located in the cheek and oral cavity but larynx localization is too rare. In this paper clinical findings of a 56-year-old- male patient with pyogenic granuloma of epiglottis was presented, differential diagnosis and treatment was discussed.
Keywords: Pyogenic granuloma; epiglottis; larynx